Exploring Photon Travel through Atomic Structures: Dynamics, Interactions, and Implications - Sah, Shyam Kishor (International Research Journal of MMC, 2025)
The investigation into how photons travel on atoms forms an essential aspect of understanding atomic and quantum physics. This study focuses on clarifying the fundamental principles that govern photon behaviour, including absorption, emission, scattering and quantum transitions. This research paper seeks to provide a comprehensive analysis of the mechanisms by which photons interact and move through atomic structures. Understanding these processes is crucial as they underpin fundamental atomic interactions and the behavior of matter at its most basic level. Through a detailed exploration of both theoretical frameworks and experimental evidence, the study identifies that photon travel is fundamentally governed by quantum probability, discrete energy-level transitions, and the dynamic interaction between photons and atomic electrons, the paper aims to elucidate the processes governing photon movement. By leveraging insights from various scholarly sources, this research aspires to contribute significantly to the existing body of knowledge and provide thoughtful implications for future studies in the field. This study will benefit researchers, physicists, and students working in quantum physics and atomic science by deepening their understanding of photon-atom interactions.